1982
DOI: 10.1289/ehp.8246117
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of organic drinking water contaminants: trichloromethane, bromodichloromethane, dibromochloromethane and tribromomethane.

Abstract: This study evaluated the subchronic toxicity of selected halomethanes which are drinking water contaminants. The compounds studied were trichloromethane, bromodichloromethane, dibromochloromethane and tribromomethane. Subchronic 14-day gavage studies were performed with the use of doses encompassing one-tenth the LD50 for the compounds. A 90-day gavage study of one of the compounds, trichloromethane, was also done. Parameters observed included body and organ weights, histopathology, hematology, clinical chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…Most mechanistic studies suggest that THMs may increase asthma risk by inducing perturbations of the immune system. In animal studies, Munson and colleagues reported depressed humoral and cellular immunity in mice after administration of BDCM or DBCM [26]. Auttachoatet and colleagues observed decreased numbers of blood circulating neutrophils in female B6C3F1 mice when TCM exposure occurred via drinking water [27].…”
Section: Discussionmentioning
confidence: 99%
“…Most mechanistic studies suggest that THMs may increase asthma risk by inducing perturbations of the immune system. In animal studies, Munson and colleagues reported depressed humoral and cellular immunity in mice after administration of BDCM or DBCM [26]. Auttachoatet and colleagues observed decreased numbers of blood circulating neutrophils in female B6C3F1 mice when TCM exposure occurred via drinking water [27].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a handful of animal studies points towards an immunosuppressive effect of DBPs in drinking water. Munson et al (1982) reported immunosuppression in mice after administration of BDCM or DBCM ; Exon et al (1987) reported immunosuppression in rats after high doses to chlorinebased disinfectants, Ueno et al (1999) reported suppression of immune responses in mice after exposure to chlorinated humic acid-concentrate as a mixture of chlorination by-products, and Auttachoat et al (2009) observed a decreased number of circulating neutrophils in blood of mice exposed to chloroform, though neutrophil function in lung homogenates was not compromised. French et al (1999) found no effects of BDCM on the immune function of mice and rats after exposure through drinking water and oral gavage.…”
Section: Independent Effects Of Dbps On Immune Markersmentioning
confidence: 99%
“…Evidence for potential immunotoxic effects of DBPs is available from a handful of animal studies (Auttachoat et al, 2009;French et al, 1999;Munson et al, 1982), while studies among humans exposed to halocarbons that are structurally very similar to DBPs also provide evidence for immunotoxic effects (Bassig et al, 2013;Griffin et al, 2000;Iavicoli et al, 2005;Weber et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Munsonetal. (1982) [14] detected in their research that chlorinated organic compounds (chloroform, tetrachloromethane, BDCM, and others) exert adverse impacts on the digestive organs, urinary excretion organs, the circulatory, nervous, and hormonal systems under oral exposure. Some COCs are carcinogenic [15][16][17][18][19].…”
mentioning
confidence: 99%